Liberté pour les patriotes palestiniens detenus dans les geoles israeliennes!
Ink cartoon of a Palestinian locked in a cell; barbed wire tower and Israeli guard mounted on top Poster advertising campaign for release of Palestinian prisoners from Israeli prisons PO-1554